2018
DOI: 10.1021/acsphotonics.7b01228
|View full text |Cite
|
Sign up to set email alerts
|

Tailored UV Emission by Nonlinear IR Excitation from ZnO Photonic Crystal Nanocavities

Abstract: For many applications in photonics, e.g., free-space telecommunication, efficient UV sources are needed. However, optical excitation of such sources requires photons of even higher energies, which are difficult to integrate into photonic circuits. Here, we present photonic crystal devices based on zinc oxide (ZnO) that allow excitation using highly abundant sources in the near-infrared (NIR). These devices offer control of generating tailored photonic modes in the UV range via higher order nonlinear processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 47 publications
0
6
1
Order By: Relevance
“…Remarkably, such a mode volume is 2.6× as small as hybrid NW-induced 2D PhC nanocavities based on the same material system. 8 It is also significantly smaller than the bulk ZnO PhC cavities that we mentioned earlier 18 and it is of the same order as what is typically obtained in monolithic III-nitride nanobeam PhC cavities operating at similar wavelengths. 22,23 The intensity enhancement ratios of the donor-like modes (Figure 4c) are significantly higher than what has been obtained in ZnO NW-induced nanocavities in 2D PhCs: we here find ratios as high as S/B = 56 in a PhC disk, with n = 36 and sf = 0.95, as compared with a maximum of S/B = 3.5 in 2D PhCs.…”
contrasting
confidence: 52%
See 2 more Smart Citations
“…Remarkably, such a mode volume is 2.6× as small as hybrid NW-induced 2D PhC nanocavities based on the same material system. 8 It is also significantly smaller than the bulk ZnO PhC cavities that we mentioned earlier 18 and it is of the same order as what is typically obtained in monolithic III-nitride nanobeam PhC cavities operating at similar wavelengths. 22,23 The intensity enhancement ratios of the donor-like modes (Figure 4c) are significantly higher than what has been obtained in ZnO NW-induced nanocavities in 2D PhCs: we here find ratios as high as S/B = 56 in a PhC disk, with n = 36 and sf = 0.95, as compared with a maximum of S/B = 3.5 in 2D PhCs.…”
contrasting
confidence: 52%
“…It is worth noting that this experimental quality factor is about an order of magnitude higher than what has been recently reported in bulk ZnO PhC nanocavities. 18 This highlights the advantage of our hybrid approach to limit scattering losses when dealing with materials such as ZnO that are especially difficult to process. Note that it is possible to achieve higher quality factors in some ZnO-based resonators fabricated through bottom-up methods that do not require any top-down processing: for example whispering-gallery modes with quality factors close to 4000 can be obtained in ZnO microwires, but at the expense of a larger mode volume.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the discovery of ZnO and its usefulness in varieties of applications, it has attracted increasing attention as promising semiconducting material [1][2][3][4][5]. Apart from gas sensing, ZnO has attracted high technological applications, like photodetectors, photodiodes, surface acoustic wave filters, solar cells, photonic crystals, LEDs, optical waveguides, due to its wide direct band gap (3.3 eV) and large excitation binding energy (60 meV) [6][7][8][9][10][11][12]. In the state of the art, doping of noble metals like gold (Au), platinum (Pt), ruthenium (Ru), nickel (Ni), palladium (Pd), gallium (Ga), silver (Ag) and their combinations showed significant improvement in ZnO-based gas sensor [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Large binding and wide bandgap energies are important factors in semiconductors and their related industrial applications, therefore researchers focused on zinc oxide and zinc oxide-based devices [1][2][3][4][5][6][7][8]. Although ZnO-based semiconductors show promise for many commercial and technological applications, it is observed that they still often do not perform as desired.…”
Section: Introductionmentioning
confidence: 99%